2020
DOI: 10.1111/cge.13742
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense variant in NME5 causes human primary ciliary dyskinesia with radial spoke defects

Abstract: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous disorder characterized by defects in the function or structure of motitle cilia. In most cases, causative variants result in axonemal dynein arm anomalies, however, PCD due to radial spoke (RS) and central pair (CP) of microtubules has been rarely reported. To identify the molecular basis of PCD characterized by RS/CP defects, we performed whole exome sequencing in PCD patients with RS/CP defects. We identified a homozygous nonsense variant (c.572… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The main limitation of our study is the PCD genes that are not part of the panel either because they were identified in the last two years and were not incorporated in the multigene panel or are yet unknown. The genes identified during the last two years include CFAP57 (Bustamante‐Marin et al, 2019), CFAP221 (Bustamante‐Marin et al, 2020), NEK10 (Chivukula et al, 2020), NME5 (Cho et al, 2020), LRRC56 (Bonnefoy et al, 2018), TTC12 (Thomas et al, 2020), DNAH9 (M. R. Fassad, Shoemark, Legendre et al, 2018), FOXJ1 (Wallmeier et al, 2019), and GAS2L2 (Bustamante‐Marin et al, 2019). Due to significant pseudogene interference, we also did not perform a comprehensive analysis of the HYDIN gene and only exons 1–5 were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of our study is the PCD genes that are not part of the panel either because they were identified in the last two years and were not incorporated in the multigene panel or are yet unknown. The genes identified during the last two years include CFAP57 (Bustamante‐Marin et al, 2019), CFAP221 (Bustamante‐Marin et al, 2020), NEK10 (Chivukula et al, 2020), NME5 (Cho et al, 2020), LRRC56 (Bonnefoy et al, 2018), TTC12 (Thomas et al, 2020), DNAH9 (M. R. Fassad, Shoemark, Legendre et al, 2018), FOXJ1 (Wallmeier et al, 2019), and GAS2L2 (Bustamante‐Marin et al, 2019). Due to significant pseudogene interference, we also did not perform a comprehensive analysis of the HYDIN gene and only exons 1–5 were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…(Hayes et al, 2007;Bontems et al, 2014;Jerber et al, 2014;Schueler et al, 2015; S7. Suga et al, 2016;Milic et al, 2017;Rabinowicz et al, 2017b;Álvarez-Satta et al, 2017;Cho et al, 2020;Shohayeb et al, 2020) We also found that STIL expression showed a negative correlation with multiple BBS genes, such as BBS1, BSS2, BBS5, BBS12, etc. On the contrary, STIL expression was positively correlated with GLI proteins (Figure 4A).…”
Section: Molecular Mechanisms and Biological Functions Of Stilmentioning
confidence: 69%
“…Studies using zebrafish as a model not only reproduced ciliary defects observed in PCDaffected individuals but also helped to understand the molecular basis of such defects. Among PCD-related genes functionally studied in zebrafish embryos are genes encoding (i) factors required for cilia assembly and cell polarity: Foxj1 homologs [265,266], and MCIDAS/multicilin [267], (ii) cytoplasmic proteins required for dynein arm assembly (see Table 1 in [152] for a full list and references), (iii) proteins required for ODA docking: CCDC151 [268], ARMC4 [269], TTC25 [270], CCDC103 [91], (iv) a molecular ruler protein CCDC40 [271], N-DRC subunits CCDC65/DRC2 [111] and GAS8/DRC4 [272,273], radial spoke components RSPH9 [94,274] and NME5 (Nucleoside diphosphate kinase 5) [275], and central pair-associated protein STK36/Fu [276].…”
Section: Aquatic Vertebrates-when a Plethora Of Siblings And Fast Dev...mentioning
confidence: 99%